2014
DOI: 10.15282/ijleal.v1.418
|View full text |Cite
|
Sign up to set email alerts
|

Investigating L2 Students’ Listening Anxiety: A Survey at a Malaysian University

Abstract: Listening anxiety is said to have a direct effect on listeners’ abilities to comprehend what has been said. This is often because listeners are concerned that the message is so complex that they will not be able to understand what they are listening to. In relevance to listening tests, students’ listening anxiety may prove to be a variable that could affect their listening test scores especially for second language (L2) learners. This preliminary study was carried out, as a part of a bigger experimental study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Meskipun terkategori sedang tetapi hal ini cukup memberikan dampak bagi kemampuan siswa dalam menguasai keterampilan menyimak. Seperti yang disampaikan oleh Tahsildar & Yusoff (2014) bahwa kecemasan dapat dikatakan apat memberikan efek secara langsung pada kemampuan mendengar siswa dalam memahami isi rekaman yang diperdengarkan. Hal ini juga dikarenakan siswa sangat merisaukan tentang pesan yang cukup kompleks yang mereka akan kesulitan dalam memahami apa yang mereka dengarkan.…”
Section: Hasil Dan Pembahasanunclassified
“…Meskipun terkategori sedang tetapi hal ini cukup memberikan dampak bagi kemampuan siswa dalam menguasai keterampilan menyimak. Seperti yang disampaikan oleh Tahsildar & Yusoff (2014) bahwa kecemasan dapat dikatakan apat memberikan efek secara langsung pada kemampuan mendengar siswa dalam memahami isi rekaman yang diperdengarkan. Hal ini juga dikarenakan siswa sangat merisaukan tentang pesan yang cukup kompleks yang mereka akan kesulitan dalam memahami apa yang mereka dengarkan.…”
Section: Hasil Dan Pembahasanunclassified
“…The learners' lack of linguistic knowledge is one of the internal factors of anxiety while listening. The unfamiliar or difficult vocabulary or sentences used in the texts makes students find themselves unable to understand every detail of the message or even incapable to make sense of the listening material (Tahsildar & Yusoff, 2014;Young, 1992). Furthermore, students' attitude and motivation also highly impacted learning anxiety.…”
Section: Factor Contributing Foreign Language Listening Anxietymentioning
confidence: 99%
“…The anxiety score is derived by adding up the 33 items with a total score of 165. The questionnaire had been used to measure learners' anxiety levels in China (Wang & Cha, 2019), in Iran (Ebadi & Oroji, 2016), and among Malaysian University students (Tahsildar & Yusoff, 2014). In this study, to answer the first research question, each student total score in FLLAS survey is analysed.…”
Section: Instrumentsmentioning
confidence: 99%
“…Though in L2 literature perhaps not as popular as L2 speaking anxiety and reading anxiety highlighted by Horwitz and associates (Horwitz, 2001;Saito, Horwitz, & Garza, 1999), L2 listening anxiety was repeatedly reported as a detrimental factor negatively affecting L2 learning in various learning contexts (Prastiyowati, 2019;Tahsildar & Yusoff, 2014;Tayşi, 2019). These findings suggested that listening anxiety played a part in affecting L2 learning.…”
Section: Introductionmentioning
confidence: 99%